Constraints of Platform-Based Learning Among Mobile-Only Students in Regional Higher Education Institutions: A Qualitative Study in the PG-PAUD Study Program - Agus Salim (Journal of Social Research, 2026)
Platform-based digital learning has become commonplace in higher education; however, its implementation often fails to accommodate students who depend on low-end smartphones as their primary learning device (mobile-only learners). This study examines the challenges of platform-based learning experienced by mobile-only students in the PG-PAUD (Pendidikan Guru Pendidikan Anak Usia Dini; Early Childhood Teacher Education) program at Universitas PGRI Argopuro Jember, representing a regional higher education context. Using a descriptive qualitative design, the study involved ten purposively selected students. Data were gathered through semi-structured online interviews and light observation of Google Classroom, Moodle/SPADA, and Zoom usage over one semester and were analyzed thematically. The results identify four key challenges: (1) low-end device limitations (restricted RAM/storage, app crashes, and difficulty accessing large files), (2) high internet data demands, particularly during synchronous sessions, (3) unstable network connectivity, and (4) platform navigation that is not mobile-friendly. These barriers are not merely technical; they contribute to an adaptive-passive participation pattern that affects engagement, timely assignment submission, and learning comprehension. The study argues that platform-based learning challenges among mobile-only students reflect structural digital inequality, thereby requiring more inclusive digital instructional design (lightweight materials, calibrated asynchronous dominance, and file-size standards) alongside institutionally responsive policies.